Green synthesized zinc oxide nanoparticles with lemongrass essential oil for the development of an effective herbal mouthwash - Preeti Pallavi; Pragnya Paramita Sahoo; Adyasha Anapurba Sahoo; Sudip kumar Sen; Sangeeta Raut (Scientific Reports)
Abstract Oral pathogens contribute to dental caries and other infections affecting oral health. To address concerns related to the adverse effects of chemical mouthwashes like chlorhexidine (CHX), this study introduces a novel herbal mouthwash formulated with green-synthesized zinc oxide nanoparticles (ZnONPs) infused with Cymbopogon citratus essential oil (CEO). Unlike traditional formulations, this herbal mouthwash aims to offer a safer, eco-friendly alternative. Four formulations (F1-F4) with varying concentrations of CEOZnONPs were evaluated for in vitro antibacterial and anti-biofilm activities against Streptococcus mutans, Staphylococcus aureus, and Escherichia coli. The F4 formulation demonstrated superior antibacterial efficacy, with inhibition zones of 64.2 ± 2.6 mm for S. mutans, 43.6 ± 1.0 mm for S. aureus, and 31.8 ± 1.5 mm for E. coli, and achieved 97.12% biofilm inhibition of S. mutans. Additionally, in vivo toxicity was assessed using embryonic zebrafish, showing a high survival rate of 93% for F1 and 82% for F4 after 24 hours, compared to 65% for CHX, indicating lower toxicity. This preclinical study shows that the F4 formulation exhibited promising antibacterial and safety profiles, highlighting its potential as a safe, natural oral care product targeting diverse oral pathogens with reduced toxicity. Further research, including in vivo and clinical trials, is needed to validate its effectiveness and safety for regular dental care use. The herbal mouthwash formulated with CEOZnONPs demonstrates strong antibacterial and anti-biofilm effects with lower toxicity, making it a promising natural alternative for oral hygiene. Its safer profile compared to CHX may reduce side effects in patients, potentially enhancing compliance in oral care regimens.